PENERAPAN MODEL PROBLEM SOLVING PADA PEMBELAJARAN KESETIMBANGAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN AKTIVITAS BELAJAR SISWA - Ahzan, Sukainil; Sunarti, Endah (Jurnal Ilmiah IKIP Mataram, 2019)
This study aims to determine whether the application of problem solving models can improve students’ understanding of concepts and learning activities. The learning model in this study is Problem Solving to familiarize students with developing the process of thinking in solving a problem with structured steps, so students better understand concepts and are active in the learning process. The sample in this study were students of class X1 Science 4 SMAN 7 Mataram. This type of research is PTK which consists of two cycles. Data collection methods use the test method, and documentation. The results showed that the application of the Problem Solving model could improve students’ understanding of concepts and learning activities.